Determinar las especies vegetativas existentes en el parque San Francisco perteneciente a la ciudad de Latacunga, provincia Cotopaxi -2022. - Chasi Mora, Katherine Estefanía (2023)
The present work was carried out in one of the parks of the city of Latacunga "San Francisco" of the parish La Matriz belonging to the canton Latacunga, province of Cotopaxi. The main objective was to determine which plant species are found in the park, in order to obtain evidence, therefore, an inventory of botanical collection and a graphic memory. The type of research that was used for the recognition of species was field-based since information and plant material were obtained, later bibliographic review was used for search, data processing and compilation of information obtained, descriptive research allowed us to systematically specify the family, genus and species of the copies obtained. The methodology for the herbal process was proposed by (Ricker, 2019) in its "Manual for botanical collection." The results recognized 30 species and 29 families, where it can be observed that the family that predominates are Asteraceae with 13%, followed by Malvaceae, Verbenaceae and Poaceae with 7%, thus having the other families with 3%. In addition, 29 genera were also identified.